The Importance of Value-based Education in the Development of Human Beings: A critical analysis of Horatio Alger’s Ragged Dick - AGUESSY, ANNE NATHALIE JOUVENCIA AGOSSI (My University, 2020)
Education, as acquirement of knowledge, abilities, values, beliefs and traditions has always been a keystone of personal and societal development. The importance of formal education to pull oneself up in the society has been inspired by Frank Whitney to Dick, the hero and main character of the novel Ragged Dick. Dick's friend Frank, saw in formal education, the key to success in the American society even if Dick is born to socioeconomic misfortune. But Ragged Dick's inner values added to the acquired education opened to him a new horizon. The objective of this paper is to show that formal education does not automatically bring success but the education based on values. Dick's love and heart have earned him successive admirations. Therefore, could education without values endanger the development of human beings? This study draws on New Historicism for theoretical insight and orientation.
Keywords: Ragged Dick – Value-based education- Inner values- Education- Human development